2007
DOI: 10.1111/j.1742-6723.2007.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Australasian emergency physicians: A learning and educational needs analysis. Part Four: CPD topics desired by emergency physicians

Abstract: This information may assist in the planning of future educational interventions for emergency physicians. EP seek CPD on management, educational and other non clinical skills, as well as topics relating directly to patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 4 publications
2
31
1
Order By: Relevance
“…In these three traditional domains, our results parallel those in Dent et al's survey 26 of fellows of the Australian College, with an emphasis on applying teaching acumen in everyday practice, managing conflict, and utilizing research results, more than conducting the research itself. However, much of their paper was oriented strongly towards CPD, whereas our results expand on the FD needs of AEPs outside of the retention/development of clinical skills.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…In these three traditional domains, our results parallel those in Dent et al's survey 26 of fellows of the Australian College, with an emphasis on applying teaching acumen in everyday practice, managing conflict, and utilizing research results, more than conducting the research itself. However, much of their paper was oriented strongly towards CPD, whereas our results expand on the FD needs of AEPs outside of the retention/development of clinical skills.…”
supporting
confidence: 77%
“…AEPs were motivated to participate in FD activities because it was personally satisfying, provided career diversity, and enhanced both teaching and leadership skills. Unlike Huwendiek et al's study, 26 which suggested that a lack of academic recognition is a barrier to FD participation, Canadian AEPs were ambivalent about peer or faculty recognition for FD participation. Moreover, AEPs opposed making FD activities mandatory (Likert response: 2/5).…”
Section: Fd Activities Need To Be Relevant and Convenientcontrasting
confidence: 63%
See 2 more Smart Citations
“…There has been a limited focus specifically on CPD in EM; [11][12][13][14][15][16][17][18] however, most medical CPD research is generally applicable to any medical specialty. There is a reasonably strong association between certified assessment of training and future clinical performance.…”
Section: Effectiveness Of Cpdmentioning
confidence: 99%